2015
DOI: 10.1007/s12639-015-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between in-house indirect ELISA and Dot-ELISA for the diagnosis of Fasciola gigantica in cattle

Abstract: This survey was done to investigate the efficacy of the in-house indirect ELISA (iELISA) and Dot-ELISA methods Prepared from excretion-secretory (ES Ag) and Crude (Cr Ag) antigens of Fasciola for sero-diagnosis of Fasciola gigantica in cattle. The liver specimens of slaughtered cattle were collected and their liver examined macroscopically and microscopically for infestation to fasciolosis. Sera from two groups of cattle, one infected with fasciolosis (n = 60) and the other non-infected with fasciolosis (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The SDS-PAGE analysis of Fg-E/S antigens in the present study showed that many bands have appeared, and the most prominent of which were of 15, 17, 28, 40, 60 and 84 kDa. Some bands (40, 60, and 84) were shown to be derived from the worm tegument (Viyanant et al, 1997), and they are the major recognition targets in ESP-based immunodiagnosis, while the 15,17 and 28 kDa species appeared to be released from the cells lining the gut (Anuracpreeda et al, 2006;Arjmand Yamchi et al, 2016). (Awad et al, 2009) showed that the Fg-ES antigen revealed seven protein bands with molecular weights of 15, 28, 31.6, 32.9, 39.4, 83.3 and 101.7 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…The SDS-PAGE analysis of Fg-E/S antigens in the present study showed that many bands have appeared, and the most prominent of which were of 15, 17, 28, 40, 60 and 84 kDa. Some bands (40, 60, and 84) were shown to be derived from the worm tegument (Viyanant et al, 1997), and they are the major recognition targets in ESP-based immunodiagnosis, while the 15,17 and 28 kDa species appeared to be released from the cells lining the gut (Anuracpreeda et al, 2006;Arjmand Yamchi et al, 2016). (Awad et al, 2009) showed that the Fg-ES antigen revealed seven protein bands with molecular weights of 15, 28, 31.6, 32.9, 39.4, 83.3 and 101.7 kDa.…”
Section: Discussionmentioning
confidence: 99%